Ebenezer Foote family papers - Foote, Ebenezer, 1756-1829.; Foote, Charles Augustus, 1785-1828.; Foote, Charles Augustus, 1818-1883.; Foote, Frederick Parsons, 1783-1827.; Foote, Harriet, 1773-1842.; Foote, Justin, 1762-; Foote, Rensselaer, 1815-1862.
Family and general correspondence, orders, petitions, legal records, and other papers of Foote and various members of his family including Charles Augustus Foote (1785-1828), Charles Augustus Foote (1818-1883), Frederick Parsons Foote, Harriet Foote, Justin Foote, and Rensselaer Foote. Subjects include the Tammany Society, or Columbian Order (N.Y.), the death of Alexander Hamilton, the War of 1812, the incident aboard the frigate Chesapeake in 1813, the first Seminole War, and New York State politics.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Continental Army officer, jurist, merchant, and legislator, of Delaware County, N.Y.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hamilton, Alexander, -- 1757-1804 -- Death and burial; Foote family; Chesapeake (Frigate); Tammany Society, or Columbian Order (N.Y.); Indians of North America -- Wars -- 1815-1875.; Seminole War, 1st, 1817-1818.; Delaware County (N.Y.) -- History; New York (State) -- Politics and government; United States -- History -- War of 1812.; Army officers; Jurists; Legislators -- New York (State); Merchants